The impact of strategic marketing on business performance - Fernandes, Ana Patrícia Carvalho (2022)
This study intends to develop an interdisciplinary relationship between Business Strategy and Strategic Marketing to identify which are the determinant variables for business performance. The main objective of this study is to understand how the variables Market Orientation and Innovation Orientation, considered part of Strategic Marketing, affect business performance. An empirical study using the quantitative method was developed, in which companies from the district of Braga were studied by using a questionnaire as a data collection instrument. This study, as performance studies in general, contributes to both managerial decision-making and academic discussion by offering relevant empirical evidence about key company success factors. This thesis allows having more recent and specific data on Strategic Marketing and Business Performance, based on the companies from the region of Braga. Firstly, it revealed a positive effect of Market Orientation and Innovation Orientation on Business Performance. Secondly, it clarifies which components of 4P’s are more influential on Business Performance. Finally, it contributes to management literature that suggests Market Orientation and Innovation Orientation ensure Business Performance success.